Microstructure, mechanical properties and corrosion behaviour of Incoloy 825 manufactured using wire arc additive manufacturing. (September 2022) - Rajkumar, V.; Vishnukumar, M.; Sowrirajan, M.; Rajesh Kannan, A.
Abstract: The microstructural features, mechanical properties, and corrosion performance of Incoloy 825 manufactured using the wire arc additive manufacturing (WAAM) process are examined. Metallographic observations revealed that the microstructure was mainly dendritic, along with the presence of precipitates and laves phases. The average tensile properties of the WAAM-printed Incoloy 825 specimens are YS-274 ± 6 MPa, UTS-576 ± 15 MPa & EL-48 ± 1.5% and YS-261 ± 9 MPa, UTS-560 ± 19 MPa & EL-53.5 ± 2% in horizontal and vertical orientations, respectively. Microhardness values varied from bottom to top (226–262 HV). The electrochemical corrosion test outcomes in 3.5% NaCl solution highlighted the stability of the WAAM-printed Incoloy 825 samples with an outstanding corrosion rate of 0.59–0.70 mils per year (mpy). Experimental results confirmed the comparable mechanical properties and superior corrosion resistance of Incoloy 825 for marine environments. Highlights: Incoloy 825 wall component was successfully fabricated with WAAM technology. Corrosion performance of WAAM-printed Incoloy 825 was studied for the first time. The microstructure was mainly dendritic along with precipitates and laves phases. Tensile samples in horizontal and vertical orientations exhibited variation. Pitting resistance was outstanding (<1 mpy) with a corrosion rate of 0.59–0.70 mpy.